2012
DOI: 10.1108/01435121211279821
|View full text |Cite
|
Sign up to set email alerts
|

Users' searching behaviour in using online databases at Vietnam National University – Ho Chi Minh City

Abstract: Purpose: This paper focuses on identifying the searching behaviors of the users, their difficulties as well as their expectations from library supports while using online databases at the Central Library of Vietnam National University-Ho Chi Minh city. Methods: Usage Reports of six online databases subscribed by the Central Library were analyzed and a survey by emailing users a questionnaire was conducted. Findings: The amount of usage increases yearly, however it is still low in comparison with the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Roy & Kumar 18 suggested that user's interface of electronic resources and databases are very complicated, due to which the usage of resources decreases. Sinh & Nhung 19 found that users are facing main problem while searching online databases and journals due to poor search skills, complex interface, less knowledge of english languages and slow internet speed.…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…Roy & Kumar 18 suggested that user's interface of electronic resources and databases are very complicated, due to which the usage of resources decreases. Sinh & Nhung 19 found that users are facing main problem while searching online databases and journals due to poor search skills, complex interface, less knowledge of english languages and slow internet speed.…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…However, a quarter of the libraries offered ILS as a voluntary training session. The findings were consistent with ALA's, (2008), IFLA's (2012) and Sinh and Nhung's (2012) view that LIS professionals should always help and support users with their information searching, including offering information literacy skills training to library clients.…”
Section: Application Of Ethics In Librariessupporting
confidence: 87%
“…According to Sinh and Nhung (2012), online databases were an essential, valuable and up-todate source of information that was being provided by LIS professionals in universities worldwide, and were indispensable to the learning, teaching and research activities of university communities. The core purpose of online databases is to retrieve useful information for the user that fully or somewhat matches the user's search inquiry (Khan, 2016).…”
Section: Online Databasesmentioning
confidence: 99%
See 1 more Smart Citation